Inhibition of angiopoietin-1 (ANGPT1) affects vascular integrity in ovarian hyperstimulation syndrome (OHSS) - Scotti, Leopoldina (2014)
Ovarian hyperstimulation syndrome (OHSS) is a complication of ovarian stimulation with gonadotrophins following human chorionic gonadotrophin (hCG) administration. The relationship between hCG and OHSS is partly mediated via the production of angiogenic factors, such as vascular endothelial growth factor A (VEGFA) and angiopoietins (ANGPTs). Here, we investigated the effect of ANGPT1 inhibition on ovarian angiogenesis in follicular fluid (FF) from women at risk of OHSS, using the chorioallantoic membrane (CAM) of quail embryos as an experimental model. We also analysed cytoskeletal changes and endothelial junction protein expression induced by this FF in the presence or absence of an ANGPT1-neutralising antibody in endothelial cell cultures. The presence of this antibody restored the number of vascular branch points and integrin avb3 levels in the CAMs to control values. ANGPT1 inhibition in FF from OHSS patients also restored the levels of claudin-5, vascular endothelial cadherin and phosphorylated b-catenin and partially reversed actin redistribution in endothelial cells. Our findings suggest that ANGPT1 increases pathophysiological angiogenesis in patients at risk of OHSS by acting on tight and adherens junction proteins. Elucidating the mechanisms by which ANGPT1 regulates vascular development and cell?cell junctions in OHSS will contribute to identifying new therapeutic targets for the treatment of human diseases with aberrant vascular leakage